2000
DOI: 10.1021/tx000133y
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Cytochrome P450 2B1 by Benzyl Isothiocyanate, a Chemopreventative Agent from Cruciferous Vegetables

Abstract: A series of arylalkyl isothiocyanates were evaluated for their ability to inactivate purified cytochrome P450 2B1 in a reconstituted system. Benzyl isothiocyanate (BITC) and phenethyl isothiocyanate (PEITC) occur naturally in several cruciferous vegetables, and the inhibition of cytochrome P450 (P450) enzymes has been implicated in their chemopreventative abilities. The naturally occurring isothiocyanates BITC and PEITC inactivated P450 2B1 in a time- and concentration-dependent manner, whereas the synthetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Previous reports (4,10,17,20,26) have shown that CYP3A4, CYP1A2, CYP2D6, and CYP2E1 are involved in the metabolism of AA. In addition, it has been reported that ITCs had an inhibitory effect on CYP activity (6,7,12,14,23). In our experiment, the plasma level and AUC 0-120 of AA and the AUC 0-120 of AA-G were raised by pretreatment with kale, whereas there were no changes in the plasma levels or pharmacokinetics parameters of AA-S.…”
Section: Resultssupporting
confidence: 42%
“…Previous reports (4,10,17,20,26) have shown that CYP3A4, CYP1A2, CYP2D6, and CYP2E1 are involved in the metabolism of AA. In addition, it has been reported that ITCs had an inhibitory effect on CYP activity (6,7,12,14,23). In our experiment, the plasma level and AUC 0-120 of AA and the AUC 0-120 of AA-G were raised by pretreatment with kale, whereas there were no changes in the plasma levels or pharmacokinetics parameters of AA-S.…”
Section: Resultssupporting
confidence: 42%
“…Because the inhibitory action of ITC has been attributed to their ability to modulate xenobiotic-metabolizing enzymes (e.g., cytochrome P-450) that are required for the activation of many carcinogens or to induce Phase II detoxifying enzymes. 44,[63][64][65] . One possibility is that cytochrome P-450 are critical targets in inhibition of the chemical-induced tumorigenesis by ITC, the distinct patterns of P-450 isozymes for carcinogen activation in rats and mice may be partially responsible for the differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect of isothiocyanates on the O-deethylation of ethoxyresorufin is due, to some extent, mechanism-based inhibition associated with these compounds (Yoxall et al, 2005;Hanlon et al, 2008a). However, it is important to point out that it is the phenobarbital-inducible CYP2B enzymes that catalyse the metabolism of phenethyl isothiocyanate to the metabolite(s) liable for mechanismbased inhibition, in contrast to benzo[a]pyrene inducible CYP1 enzymes, suggesting that mechanism-based inhibition is unlikely to be the dominant mechanism (Lee, 1996;Goosen et al, 2000;Nakajima et al, 2001;Konsue and Ioannides, 2010c). Thus, it can be inferred that isothiocyanates are effective antagonist of the Ah receptor in rat and human liver, and this potential may contribute to their established chemopreventive activity.…”
Section: Interaction Of Isothiocyanates and Glucosinolates With The Amentioning
confidence: 99%